2002
DOI: 10.1128/jvi.76.5.2403-2409.2002
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Preferentially Transduces the Basolateral Surface of Well-Differentiated Human Airway Epithelia

Abstract: Measles virus (MV) is typically spread by aerosol droplets and enters via the respiratory tract. The progression of MV infection has been widely studied; yet, the pathway for virus entry in polarized human airway epithelia has not been investigated. Herein we report the use of a replication-competent Edmonston vaccine strain of MV expressing enhanced green fluorescent protein (MV-eGFP) to infect primary cultures of well-differentiated human airway epithelia. Previous studies with polarized Caco-2 cells (intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 29 publications
9
63
3
Order By: Relevance
“…Lymphocytes disseminate infection in the organism; in particular, epithelia are infiltrated by lymphocytes that occasionally may succumb to the infection load and locally release virus. Lung epithelium infection may be initiated from the basal side, consistent with the observation that MV preferentially transduces the basolateral surface of welldifferentiated human airway epithelia (31). This sequence of events is different from previous morbillivirus infection models: based on limited evidence, it was assumed that the initial MV infection is established in the respiratory tract (2,3).…”
Section: Discussionmentioning
confidence: 85%
“…Lymphocytes disseminate infection in the organism; in particular, epithelia are infiltrated by lymphocytes that occasionally may succumb to the infection load and locally release virus. Lung epithelium infection may be initiated from the basal side, consistent with the observation that MV preferentially transduces the basolateral surface of welldifferentiated human airway epithelia (31). This sequence of events is different from previous morbillivirus infection models: based on limited evidence, it was assumed that the initial MV infection is established in the respiratory tract (2,3).…”
Section: Discussionmentioning
confidence: 85%
“…It remains to be determined if such variation is linked to either differences in the extent of epithelial disruption or the virus burden in the epithelium of the URT. Although in vitro studies have shown that epithelial cells can be infected by MV and produce new virus particles by budding from the apical membrane (Sinn et al, 2002;Tahara et al, 2008;Takeuchi et al, 2003), MV cell-to-cell spread is relatively slow and results in the release of low virus titres (Leonard et al, 2008;Ludlow et al, 2010;Mühlebach et al, 2011). In contrast, the MV replication cycle in lymphocytes is usually more rapid and results in higher levels of viral shedding (de Vries et al, 2010a;Lemon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Human CD46 primarily is expressed on the basolateral surfaces of polarized epithelial cells, 42,43 and measles virus preferentially infects cells from their basolateral, rather than apical, sides. 44 Anatomical barriers such as the tightness between the basal membrane and extracellular matrix might impair the access of Ad35 vectors to the human CD46 on the basolateral cell surface. Another possibility is that an unidentified receptor or co-receptor for Ad35 is expressed in humans but not in CD46TG mice.…”
Section: Ad35 Vector-mediated Transduction F Sakurai Et Almentioning
confidence: 99%